Perbandingan Kemampuan Komunikasi Matematis Siswa antara yang Mendapatkan Model Pembelajaran Problem Based Learning dengan Pendekatan Realistic Mathematics Education dan Open-Ended - Alamiah, Ulfah Syifa; Afriansyah, Ekasatya Aldila (Mosharafa: Jurnal Pendidikan Matematika, 2017)
Penelitian ini dilatar belakangi oleh rendahnya kemampuan komunikasi matematis siswa yang berdampak pada rendahnya kemampuan dalam menyelesaikan soal matematika yang menuntut kemampuan komunikasi matematis siswa. Penelitian ini bertujuan untuk mengetahui perbandingan kemampuan komunikasi matematis siswa antara yang mendapatkan model Pembelajaran Problem Based Learning dengan pendekatan Realistic Mathematics Education dan open-ended. Adapun metode penelitian yang digunakan dalam penelitian ini adalah metode quasi eksperimen yang terdiri dari dua kelas, yaitu kelas eksperimen 1 yang mendapat model pembelajaran PBL dengan pendekatan RME dan kelas eksperimen 2 yang mendapat model pembelajaran PBL dengan pendekatan Open-Ended. Penelitian dilaksanakan di SMP Negeri 1 Cikajang dengan sampel penelitiannya adalah kelas VII A sebagai kelas eksperimen 1 dan VII B sebagai kelas eksperimen 2. Materi yang dijadikan bahan penelitian yaitu tentang sistem persamaan dan pertidaksamaan linear satu variabel (SPLSV). Instrumen penelitian ini berupa tes dengan bentuk uraian yang diberikan pada saat pretest dan posttest serta diberikan tes skala sikap siswa. Dari hasil penelitian dapat disimpulkan kemampuan komunikasi matematis antara siswa yang mendapatkan model pembelajaran Problem Based Learning menggunakan pendekatan Realistic Mathematic Education lebih baik dari pada pendekatan Open-Ended. This research is based on the low ability of students & apos mathematical communication which has an impact on the low ability to solve the mathematical problems that demand the students and apos; mathematical communication ability. This study aims to determine the comparison of students and apos; mathematical communication skills between Learning Problem Based Learning Model; with Realistic Mathematics Education and open-ended approach. The benefit of this research in general is to provide an overview of PBL learning model with RME and open-ended approach to students & apos mathematical communication ability. The research method used in this research is a quasi-experimental method consisting of two classes, namely experimental class 1 which received PBL learning model with RME approach and experiment class 2 which got PBL learning model with Open-Ended approach. The research was conducted in SMP Negeri 1 Cikajang with the research sample is class VII A as experimental class 1 and VII B as experiment class 2. The material used as research material is about system of equation and linear inequality one variable (SPLSV). The instrument of this research is a test with the form of description given at the time of pretest and posttest and given the students attitude scale test. From the results obtained pretest Ho accepted so it can be concluded that there is no significant difference in students and apos; mathematical communication between experimental class 1 and experiment class 2. From the result posttest obtained Ha accepted, so it can be concluded mathematical communication skills between students who get the model of learning Problem Based Learning Using the Realistic Mathematic Education approach is better than the Open-Ended approach. While the scale of student attitudes processed with Likert scale, and it can be concluded that students interpret both the PBL learning model with the approach of RME and open-ended.